TLR9 Signaling Suppresses the Canonical Plasma Cell Differentiation Program in Follicular B Cells - Baptista, Bárbara José Antunes; Granato, Alessandra; Canto, Fábio B.; Montalvão, Fabricio; Tostes, Lucas; de Matos Guedes, Herbert L.; Coutinho, Antonio; Bellio, Maria; Vale, Andre M.; Nobrega, Alberto (Frontiers in Immunology, 2018)
The relative potency and quality of mouse B cell response to Toll-like receptors (TLRs) signaling varies significantly depending on the B cell subset and on the TLR member being engaged. Although it has been shown that marginal zone cells respond faster than follicular (FO) splenic B cells to TLR4 stimulus, FO B cells retain full capacity to proliferate and generate plasmablasts and plasma cells (PBs/PCs) with 2-3 days delayed kinetics. It is not clear whether this scenario could be extended to other members of the TLR family. Here, using quantitative cell culture conditions optimized for B cell growth and differentiation, we show that TLR9 signaling by CpG, while promoting vigorous proliferation, completely fails to induce differentiation of FO B cells into PBs/PCs. Little or absent Ig secretion following TLR9 stimulus was accompanied by lack of expression of cell surface markers and canonical transcription factors involved in PB/PC differentiation. Moreover, not only TLR9 did not induce plasmocyte differentiation, but it also strongly inhibited the massive PB/PC differentiation of FO B cells triggered by LPS/TLR4. Our study reveals unexpected opposite roles for TLR4 and TLR9 in the control of plasma cell differentiation program and disagrees with previous conclusions obtained in high-density cultures conditions on the generation of plasmocytes by TRL9 signaling. The potential implications of these findings on the role of TLR9 in controlling self tolerance, clonal sizes and regulation of humoral responses are discussed.